2019
DOI: 10.21608/ejh.2019.15565.1154
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Ultrastructure changes in the embryonic development of Schistocerca gregaria (Forskal) (Orthoptera: Acrididae) induced by Lufenuron(CSI) and Rice Bran Extract (Waste product).

Abstract: Background: Waste product compound of rice bran and lufenuron are considered safe compounds to the human and to the environment. They can be used to control Schistocerca gregaria. Objective: The aim of the present study is to examine the ultrastructural changes and histopathological alteration in the Schistocerca gregaria embryogenesis induced by selected waste product compound of rice bran (Oryza sativa) and a chitin synthesis inhibitor (lufenuron). Materials and Methods: Histological and ultrastructure study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…Also rice bran extract caused compression and loss in the brain morphic nature, and poorly developed compound eyes (F.2b). These observations are in agreement with the findings of the brain and compound eyes damage in newly hatched nymphs of S. gregaria due to lufenuron treatment reported by (Abdel Rahman, 2017), also, rice bran extract and lufenuron exhibited disruption in the histological formation of the brain and compound eyes during embryonic development in the desert locust (Mahdy et al, 2020). Similar observations showed by different plant extracts as azadirachtin on S. gregaria eggs caused poorly developed brain and compound eyes of newly hatching (Ghazawy et al, 2010), abnormal brain cells of desert locust nymphs treated with Cestrum leaf powder were observed by Ben Hamouda et al (2011).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Also rice bran extract caused compression and loss in the brain morphic nature, and poorly developed compound eyes (F.2b). These observations are in agreement with the findings of the brain and compound eyes damage in newly hatched nymphs of S. gregaria due to lufenuron treatment reported by (Abdel Rahman, 2017), also, rice bran extract and lufenuron exhibited disruption in the histological formation of the brain and compound eyes during embryonic development in the desert locust (Mahdy et al, 2020). Similar observations showed by different plant extracts as azadirachtin on S. gregaria eggs caused poorly developed brain and compound eyes of newly hatching (Ghazawy et al, 2010), abnormal brain cells of desert locust nymphs treated with Cestrum leaf powder were observed by Ben Hamouda et al (2011).…”
Section: Resultssupporting
confidence: 93%
“…The present study revealed that The tested compounds have latent histopathological effects where they induced serious changes in newly hatching of affected S. gregaria eggs with lufenuron and rice bran extract treatments and these associated with their toxic effects which were reported by Mahdy et al (2019Mahdy et al ( & 2020, where they caused a disturbance in the protein and DNA of eggs resulting from treated females as fifth nymphal instars with LC50 of them leading to histopathological variations of embryonic structure and inhibition of embryonic development and hatching in some eggs, and this explains, why some affected eggs produce abnormal newly hatched nymphs.…”
Section: The Muscles Of the Legssupporting
confidence: 60%
See 2 more Smart Citations